Molecular Identification and Phylogenetic Analysis of Nuclear rDNA Sequences of Clonorchis sinensis Isolates From Human Fecal Samples in Heilongjiang Province, China - Zhang, Xiaoli; Sun, Beibei; Tang, Qiaoran; Chen, Rui; Han, Su (Frontiers in Microbiology, 2019)
Studying the genetic diversity of parasite is important for understanding their biogeography and molecular epidemiology, as well as for establishing disease prevention and control strategies. Clonorchis sinensis is an important foodborne parasite worldwide. However, despite its epidemiological significance, the genetic diversity of C. sinensis has not been well studied from human in northeastern China. In this study, a total of 342 fecal specimens were collected from residents living in five villages in Heilongjiang Province and analyzed for the presence of C. sinensis by PCR amplification and sequencing of the internal transcribed spacer1 (ITS1) and ITS2 regions of nuclear ribosomal DNA. 21.64% (74/342) of fecal samples were found to be positive for C. sinensis by PCR. The sequences of the ITS1 region in 34 of the 74 samples (45.95%) matched that of MK179278, Genetic polymorphisms were observed at six nucleotide sites. The ITS2 gene sequence of 37 of the 74 samples (50%) matched that of MK179281. In conclusion, a low degree of genetic diversity between C. sinensis isolates from China and different geographical regions was found at ITS loci. Despite this conservation, sequencing of the rDNA region has provided important data that will be useful for future studies addressing the molecular evolution, biology, medical implications and ecology of C. sinensis.